Challenges with Takayasu arteritis in pregnancy: a case report - Dalal, Monika; Malhotra, Vani; Nanda, Smiti; Chauhan, Meenakshi; Rani, Vandana; Gautam, Sarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Takayasu’s arteritis (TA) is a rare, chronic, inflammatory, large vessel vasculitis (LVV) of unknown etiology characterized by narrowing, occlusion, and aneurysms of systemic and pulmonary arteries affecting especially the aorta and its branches. Pregnant patients are at increased risk of cardiovascular complications, including hypertension and congestive heart failure, which may jeopardize both maternal and fetal outcomes, so one should pay special attention to these patients. We present a case of 30-year-old female G5P3L2A1 with 9 months of amenorrhea with previous 2 LSCS with chronic hypertension and superimposed pre-eclampsia with oligohydraminos. She was a known case of Takayasu arteritis, diagnosed since she was 16 years old. Her lower limb pulses were palpable with absent upper limb pulses. On Echocardiography there was dilated aortic root, moderate MR and LVEF was 55%. She proceeded to have emergency LSCS under spinal anesthesia in view of severe pre-eclampsia with previous 2 LSCS at 35 week and delivered alive healthy female baby weight 2.1 kg. A life-threatening maternal cardiovascular complication is observed in more than 5% of pregnant women with TA. Hypertension is present in 90% cases of Takayasu arteritis. A good control of TA disease activity and arterial hypertension before conception and during pregnancy is important to improve feto-maternal outcomes. Pregnancies in the setting of TA should be considered high-risk, requiring a close interdisciplinary collaboration of rheumatologists, nephrologists and obstetrician’s specialists involved in care of TA.